Living by design ideas for interiors & gardens - Stefanidis, John (Weidenfeld & Nicalson, 1997)
This text takes the reader on a tour through John Stefanidis' country home, created 24 years ago from a collection of assorted outbuildings. Room by room, he reveals his secrets and offers tips. The book includes plans of the house and garden, showing how he achieves his style and effects.